Prevalence of multimorbidity and its impact on survival in people with motor neuron disease. (15th June 2021) - Glasmacher, Stella A.; Kearns, Patrick K. A.; Larraz, Juan; Stirland, Lucy; Mehta, Arpan R.; Newton, Judith; Weir, Christopher J.; Chandran, Siddharthan; Pal, Suvankar; ,
Abstract: Background and purpose: This study was undertaken to determine the prevalence of multimorbidity in people with motor neuron disease (MND) and to identify whether specific patterns of multimorbidity impact survival beyond age alone. Methods: We performed a retrospective analysis of the Scottish national MND register from 1 January 2015 to 29 October 2019. People with amyotrophic lateral sclerosis, primary lateral sclerosis, progressive muscular atrophy, or progressive bulbar palsy were included. We fitted latent class regression models incorporating comorbidities (class indicators), age, sex, and bulbar onset (covariates), and survival (distal outcome) with multimorbidity as a hypothesised latent variable. We also investigated the association between the Charlson Comorbidity Index and survival in Cox regression and compared its discrimination and calibration to age alone. Results: A total of 937 people with MND were identified (median age = 67 years, 60.2% male); 64.8% ( n = 515) had two or more comorbidities. We identified a subpopulation with high prevalence of cardiovascular disease, but when accounting for the relationship between age and individual comorbidities, there was no difference in survival. Both Charlson Comorbidity Index (hazard ratio [HR] per unit increase = 1.11, 95% confidence interval [CI] = 1.07–1.15, p  < 0.0001) and age (HR per year increase = 1.04, 95% CI = 1.03–1.05, p  < 0.0001) were significantly associated with survival, but discrimination was higher for age compared to Charlson Comorbidity Index (C‐index = 0.63 vs. 0.59). Conclusions: Multimorbidity is common in MND, necessitating holistic interdisciplinary management, but age is the dominant predictor of prognosis in people with MND. Excluding people with MND and multimorbidity from trial participation may do little to homogenise the cohort in terms of survival potential and could harm generalisability. Abstract : In this population‐based study (n=937), 64% of people with motor neuron disease had at two or more comorbidities. Age rather than multimorbidity was the dominant predictor of prognosis in people with MND.